Activation of Brainstem Neurons During Mesencephalic Locomotor Region-Evoked Locomotion in the Cat - Opris, Ioan; Dai, Xiaohong; Johnson, Dawn M. G.; Sanchez, Francisco J.; Villamil, Luz M.; Xie, Songtao; Lee-Hauser, Cecelia R.; Chang, Stephano; Jordan, Larry M.; Noga, Brian R. (Frontiers in Systems Neuroscience, 2019)
The distribution of locomotor-activated neurons in the brainstem of the cat was studied by c-Fos immunohistochemistry in combination with antibody-based cellular phenotyping following electrical stimulation of the mesencephalic locomotor region (MLR) – the anatomical constituents of which remain debated today, primarily between the cuneiform (CnF) and the pedunculopontine tegmental nuclei (PPT). Effective MLR sites were co-extensive with the CnF nucleus. Animals subject to the locomotor task showed abundant Fos labeling in the CnF, parabrachial nuclei of the subcuneiform region, periaqueductal grey, locus ceruleus/subceruleus, Kölliker-Fuse, magnocellular and lateral tegmental fields, raphe, and the parapyramidal region. Labeled neurons were more abundant on the side of stimulation. In some animals, Fos labeled cells were also observed in the ventral tegmental area, medial and intermediate vestibular nuclei, dorsal motor nucleus of the vagus, n. tractus solitarii and retrofacial nucleus in the ventrolateral medulla. Many neurons in the reticular formation were innervated by serotonergic fibers. Numerous locomotor-activated neurons in the parabrachial nuclei and locus ceruleus/subceruleus/Kölliker-Fuse were noradrenergic. Few cholinergic neurons within the PPT stained for Fos. In the medulla, serotonergic neurons within the parapyramidal region and the nucleus raphe magnus were positive for Fos. Control animals, not subject to locomotion, showed few Fos labeled neurons in these areas. The current study provides positive evidence for a role for the CnF in the initiation of locomotion while providing little evidence for the participation of the PPT. The results also show that MLR-evoked locomotion involves the parallel activation of reticular and monoaminergic neurons in the pons/medulla, and provides the anatomical and functional basis for spinal monoamine release during evoked locomotion. Lastly, the results indicate that vestibular, cardiovascular and respiratory centers are centrally activated during MLR evoked locomotion. Altogether, the results show a complex pattern of neuromodulatory influences of brainstem neurons by electrical activation of the MLR.